Evaluation of Portfolio Assessment of Student Work in Arabic Language Learning - Makfiro, Nikmatul; Hermiwati, Hermiwati; Sumiati, Sumiati; Muzadi, Narul Hasyim (Tanwir Arabiyyah: Arabic as Foreign Language Journal, 2024)
This research discusses the evaluation of portfolio assessment in Arabic learning, especially related to students' ability to understand fi'il madhi and fi'il mudhari' in the form of mabni majhul and mabni ma'lum at Pomdok Pesantern Al-Anwar Muara Jambi. The background of this study focuses on the importance of a comprehensive evaluation that not only measures the final results, but also the overall learning process of students. The purpose of the research is to evaluate work portfolios as an assessment tool in measuring student development related to Arabic grammar. The research used a qualitative approach of case study type, with data collection techniques through semi-structured interviews and documentation analysis. The data analysis technique used is the Miles and Huberman model, which involves collecting, reducing, and presenting data, as well as drawing conclusions. This study used primary data sources and secondary data sources. Primary data sources were obtained from semi-structured interviews with Ustadzah Fitriawati as well as analysis of student portfolios to assess understanding of fi'il madhi and fi'il mudhari' in the form of mabni majhul and mabni ma'lum. Secondary data sources include archived academic grade documents and learning outcome reports, as well as literature related to portfolio assessment in language education to provide a theoretical foundation and comparison with previous research.  The results showed that the use of portfolio work assessment was effective in monitoring the continuous development of students' understanding, both in theory and application of concepts. Portfolios encourage collaboration and discussion between students, and improve critical thinking skills.